DESCRIPTION OF WASTE PRINT AL-QUR'AN - Rizka Fajrin Maulidinar; MT Djamara; Yessy Yerta Situngkir (Politeknik Negeri Media Kreatif, 2020)
The Graphics Industry is an industry that designs, develops, makes, and introduces products that contain or are related to sentences and or images to realize information, ideas and feelings. The product is used for the purposes of learning, entertainment, motivating, commercial, and so on. The graphics industry in Indonesia continues to experience improvement by continuing to make improvements both in producing quality graphic products with the times without reducing the essence of the graphics itself, namely the media for delivering printed information to be presented to the public and in processing waste. The graphics production process is divided into three stages, namely preprint, print and post print. PT. Gramedia Printing Cikarang Plant, as one of the major graphics companies in Indonesia, feels the need to create a working line and system, including providing special services that are separate from other print production flows so that the product prints are perfect, namely printing services for the Al-Qur'an manuscripts. . In the flow of the printing of the Al-Qur'an manuscripts, the treatment is not arbitrary, even up to the handling of the waste. Writing this final project aims to determine whether the application of waste processing resulting from the printing of the Al-Quran is in accordance with Islamic principles and rules of occupational safety and health.Keywords: Waste, Occupational Safety and health, Printing of Al-qur'an